Clinical, Cytological, Histological and Immunohistochemical Features of Cutaneous Mast Cell Tumours in Ferrets (Mustela putorius furo). Issue 4 (November 2016) - Vilalta, L.; Meléndez-Lazo, A.; Doria, G.; Ramis, A.; Solano-Gallego, L.; Pastor, J.; Martorell, J.
Summary: Cutaneous mast cell tumours (cMCTs) are one of the most common cutaneous tumours in ferrets ( Mustela putorius furo ). However, limited information is available regarding cytological and histological features of these tumours and studies evaluating KIT expression are lacking in this species. The aims of this prospective study were to describe the most common clinical, cytological and histological features of cMCTs in ferrets and to compare the usefulness of different staining techniques in the diagnosis of these tumours in ferrets as well as evaluating KIT expression in neoplastic mast cells (MCs) by immunohistochemistry. Macroscopically, the tumours were small, round to plaque-like and frequently associated with surface crusting. The most common locations were the extremities and the trunk. MC granules were stained in all cases using toluidine blue (TB) and Wright–Giemsa stains in cytological specimens, but none stained with modified Wright's stain. Haematoxylin and eosin and TB on histological sections failed to stain MC granules in all the cases. Cytological and histological examination revealed low to moderate anisocytosis and anisokaryosis. An infiltrative rather than a delineated or encapsulated growth pattern was noted histologically in all cases. Eosinophilic infiltration was not uncommon and 'collagenolysis' was detected on cytological and histological examination. KIT expression was detected in all cases evaluated. In approximately one third of the cases the MCs exhibited KIT labelling pattern I and in the remaining ferrets, KIT pattern III. No correlation was found between KIT expression pattern and biological behaviour.